Efektivitas Latihan Handgrip Dengan Beban Tekanan 30 Kg Terhadap Peningkatan Kekuatan Otot Tangan Siswa Ekstrakurikuler Bola Voli Di SMPN 3 Sleman - Nur Cholis Majid (Journal on Education, 2023)
This study aims to determine: (1) the effect of handgrip training with a pressure load of 30 kg on increasing hand muscle strength (2) the difference in the effect of handgrip training with a pressure load of 30 kg between the treatment group and the control group on increasing hand muscle strength. This type of research is an experiment with a one group pre test and post test design. The sample in this study amounted to 77 people who were taken using a random sampling technique. Subjects were divided into 2 groups, namely the group that was given treatment as many as 36 people and the control group as many as 31 people. The instrument used is to measure hand muscle strength, namely the handgrip dynamometer test. The data analysis technique used was the independent sample t test and continued with the paired sample t-test. The results showed that: 1) There was a significant effect of handgrip dynamometer training on increasing hand muscle strength with a significance value of less than 0.05 (p <0.05). 2) There was a significant difference in the effect between the treatment group and the control group on increasing hand muscle strength, it was proven that the average hand muscle strength in the treatment group was 53.76 while the hand muscle strength in the control group was 40.75 with a post-test average difference of 13.01. The group that was given the treatment had better hand muscle strength compared to the control group that didn't get the treatment.